Connexin 43 Hemichannels Regulate the Expression of Wound Healing-Associated Genes in Human Gingival Fibroblasts - Rana Tarzemany; Guoqiao Jiang; Jean X. Jiang; Hannu Larjava; Lari Häkkinen (2017)
Connexin 43 (Cx43) is the most ubiquitous connexin in various cells, and presents as hemichannels (HCs) and gap junctions (GJs) on the cell membrane. We have recently shown that Cx43 abundance was strongly reduced in fibroblasts of human gingival wounds, and blocking Cx43 function in cultured human gingival fibroblasts (GFBLs) strongly regulated the expression of wound healing-related genes. However, it is not known whether these responses involved Cx43 HCs or GJs. Here we show that Cx43 assembled into distinct GJ and HC plaques in GFBLs both in vivo and in vitro. Specific blockage of Cx43 HC function by TAT-Gap19, a Cx43 mimetic peptide, significantly upregulated the expression of several MMPs, TGF-β signaling molecules, Tenascin-﻿C, and VEGF-A, while pro-fibrotic molecules, including several extracellular matrix proteins and myofibroblast and cell contractility-related molecules, were significantly downregulated. These changes were linked with TAT-Gap19-induced suppression of ATP signaling and activation of the ERK1/2 signaling pathway. Collectively, our data suggest that reduced Cx43 HC function could promote fast and scarless gingival wound healing. Thus, selective suppression of Cx43 HCs may provide a novel target to modulate wound healing.